0572 Impact of Upper Airway Stimulation Therapy on Clinical Blood pressure Parameters from the ADHERE Registry. (12th April 2019) - Patel, Nimit; Thompson, Nicolas; Mehra, Reena; Waters, Tina; Foldvary-Schaefer, Nancy; Kominksy, Alan; Aylor, Joan; Walia, Harneet
Abstract: Introduction: Upper airway stimulation therapy (UAS) is a recently approved therapy for moderate to severe obstructive sleep apnea. There are limited data examining the clinical blood pressure outcomes for patients treated with UAS. We hypothesize there will be significant reduction in blood pressure (BP) parameters for all patients undergoing treatment with UAS and that this reduction will be more pronounced in those who have elevated baseline BP. Methods: Clinical BP data were collected from 337 patients of Adherence and Outcome of Upper Airway Stimulation for OSA (ADHERE), which is a multinational registry. Mean change from baseline to 12 month follow up was calculated for the overall cohort and also in the subset of patients with elevated BP at baseline (American Heart Association's guideline; systolic BP ≥ 130 mm Hg or diastolic BP ≥ 80 mm Hg). Paired t-tests were performed to determine if within group change was significant. Results: Average age and BMI were 59.8 years (SD=10.6) and 29.2 kg/m 2, respectively with 19.6 % female and 97.3% Caucasian. 63.7% of patients had elevated BP at baseline. In the full cohort, no significant changes were observed for any BP parameters. In the elevated BP group there was a significant decrease in systolic BP by 4.4 mmHg {(134.9 (SD 11.1) to 130.6 (SD 12.9) mmHg)} and a decrease in mean arterial pressure (MAP) by 2.3 mmHg {(99.8 (SD 7.3) to 97.5 (SD 10.1) mmHg)} with all p values <0.001 from baseline to 12 month follow up. No significant change was observed in diastolic BP. Conclusion: While no significant BP changes were observed in the entire cohort, patients with elevated baseline BP had a significant decrease in systolic and MAP at 12 months. These findings suggest that UAS may produce selective beneficial effects on BP in patients with OSA. More rigorous prospective studies are needed to explore the BP outcomes of patients treated with UAS. Support (If Any)